ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT TIMBUL MANDIRI JAYA BOYOLALI TAHUN 2019 - Aan Irfan Adiyanto; Nuning Lisdiana; unna Ria safitri (EKOBIS, 2020)
Within a company, employees are one of the most valuable assets. Employees are human resources that drive companies to compete with other companies. Employees who have satisfaction in working will certainly be able to increase performance productivity and achieve the goals set by the company. PT Timbul Mandiri Jaya Boyolali is a company engaged in the automotive sector which is addressed at Jalan Boyolali - Semarang KM 1, Winong Village, Boyolali District, Boyolali Regency. PT Timbul Mandiri Jaya Boyolali sells Honda motorcycle products and serves Honda motorcycle services. PT Timbul Mandiri Jaya Boyolali is the largest Honda motorcycle dealer in the city of Boyolali which has 75 employees both sales and ahass, because it has quite a lot of employees of course need good management so that employees get satisfaction in working, this causes an influence on employee performance working at PT Timbul Mandiri Jaya Boyolali. This study aims to determine the effect of job satisfaction on employee performance at PT Timbul Mandiri Jaya Boyolali and which job satisfaction variables most influence employee performance at PT Timbul Mandiri Jaya Boyolali. This research was conducted at PT Timbul Mandiri Jaya Boyolali, a research period of 3 months by distributing several questionnaires with the object of Timbul Jaya Motor employees as many as 75 correspondents. Methods of collecting data using questionnaires. Analysis of the data used is multiple regression analysis and significance testing using t and F tests. The results show that there is no positive and significant effect of salary, the job itself, promotion and coworkers on employee performance, while the supervisory variable has a positive and significant influence on employee performance with t_table <t_count with a significance of more than 5% or 0.05 Keywords : Salary, Employment, Promotion, Colleagues, Supervision, and Employee Performance.